FORMULATION AND TEST INHIBITORY EFFECT OF MUSHROOMS CREAM PREPARATION ETHANOL EXTRACT AVOCADO SEEDS (PERSEA AMERICANA MILL) AGAINST MALASSEZIA FURFUR IN VITRO - Turnip, Nur Ulina M. Br.; Novandi Purba; Novidawati Boru Situmorang; Sarah Gabetta br Napitupulu (Jurnal FARMASIMED (JFM), 2023)
Avocado seeds (Persea americana Mill) are household waste that contains secondary metabolites that can be used as antifungal agents. The antifungal activity of pure ethanol extract from avocado seeds (Persea americana Mill) has been tested and shown to have inhibitory effects on the fungus Malassezia furfur. Pityriasis versicolor is one of the diseases that can be treated due to the infection of Malassezia furfur, and skin diseases are generally treated using semi-solid formulations like creams. The objective of this study is to determine the antifungal activity of a cream formulation of ethanol extract from avocado seeds against Malassezia furfur. The method used to test the inhibitory activity of the cream containing ethanol extract from avocado seeds (Persea americana Mill) against Malassezia furfur is the disc diffusion method. Phytochemical screening results indicated that the ethanol extract from avocado seeds contains alkaloids, flavonoids, tannins, and saponins. The cream containing ethanol extract from avocado seeds (Persea americana Mill) was tested at concentrations of 20% (10 grams), 40% (20 grams), and 60% (30 grams), along with a positive control of Ketoconazole 2%. The research results showed that the cream containing ethanol extract from avocado seeds (Persea americana Mill) at concentrations of 20%, 40%, and 60% exhibited inhibitory zones with diameters of 5.85 mm, 6.73 mm, and 7.66 mm, categorizing them as having a moderate inhibitory effect. Therefore, it can be concluded that the greater the concentration of the extract, the larger the diameter of the inhibitory zone." Keywords: Panu, Malassezia furfur, Antifungal, Cream, Avocado seed (Persea americana Mill).